STRATEGY TO PREVENT REVERSE REACTIONS IN WATER GAS SHIFT (WGS) THROUGH CU/ZNO NANOCATALYST WITH MFI TYPE OF ZEOLITE SUPPORT - Liska, Salma
Natural gas in the Natuna Sea with a content of 71%-mol CO2 and 28%-mol CH4 of 46 trillion standard cubic feet (TSCF) has the potential to be explored. One of the technology that can process natural gas, which is rich in CO2, into a product with a higher selling value is through dry reforming of methane (DRM). DRM can convert CH4 and CO2 into synthesis gas with a H2/CO content around 1. The presence of CO gas in DRM gas products is still relatively high, so further processing is needed to minimize CO gas and increase hydrogen productivity, one of which is the water gas shift (WGS) reaction. Commercially, the WGS reaction is carried out in 2 stages because the reaction is exothermic using Fe-based catalysts in high-temperature shift (HTS) conditions and Cu-based catalysts in low-temperature shift (LTS) conditions. However, there are limitations in the use of commercial catalysts because they can only be used under standard conditions. Therefore, it is necessary to develop further catalysts to obtain good activity and stability for the WGS reaction so that they can be used to treat product gas DRM under medium temperature shift (MTS) conditions. The MTS condition is carried out in one stage to reduce operating costs. Cu/ZnO/ZSM-5 catalyst can be used for WGS reactions under MTS conditions. Copper is economical and commonly used as the active phase of commercial catalysts. ZSM-5 is an aluminosilicate with a pore diameter of 0.54–0.56 nm. It has a high surface area, uniform pore size, and good thermal stability, making it suitable for catalyst support WGS reactions under MTS conditions. This study focused on determining the optimum loading amount of Cu metal for processing DRM gas products containing CO2, H2, and CH4 through the WGS reaction under MTS conditions. This study carried out four stages: synthesis, characterization, internal and external mass transfer tests, activity, and catalyst stability tests. Cu/ZnO/ZSM-5 catalyst was prepared by impregnation method with the loading of Cu 5, 10, and 15 %-wt with a mass ratio of Cu/Zn of 1. The activity and stability of the catalyst were tested in a fixed bed reactor, atmospheric pressure, and temperature of 325 oC with a steam to gas mixture ratio of 0.55 or steam to CO in the range of 3–4. The increase in Cu loading is directly proportional to the activity of the catalyst. The catalyst with 15%-wt Cu loading showed the best results with 35% CO conversion and 36% H2 yield and good stability for 32 hours. A commercial catalyst of 58% Cu results in a conversion of 56% CO. However, if calculated per unit mass of Cu catalyst 15% Cu/ZnO/ZSM-5 produces activity 2.4 times higher than commercial catalysts. TGA was performed on the spent catalyst to determine the amount of carbon formed. The 15% Cu/ZnO/ZSM-5 catalyst produced 0.04 g carbon/g catalyst, while the 58%-wt Cu commercial catalyst produced 0.105 g carbon/g catalyst. The presence of excess H2 and CO2 in the feed causes the CO conversion not to reach equilibrium and the selectivity to the WGS reaction does not reach 100%. The correlation between catalyst characterization results and catalyst activity test is influenced by the amount of active metal charge on the catalyst. Keywords: water gas shift reaction (WGSR), medium temperature shift (MTS), Cu/ZnO nanocatalyst, hydrogen